Сучасні науково-методичні проблеми математики у вищій школі - Національний університет харчових технологій (My University, 2018)
Видання містить матеріали Міжнародної науково-методичної конференції «Сучасні науково-методичні проблеми математики у вищій школі». На конференції розглянуті сучасні математичні методи в інженерних задачах та методичні проблеми викладання математичних дисциплін у вищій школі. У матеріалах висвітлено шляхи і методи інтенсифікації навчального процесу й вплив новітніх наукових розробок на формування майбутніх фахівців. This publication contains the materials of International Scientific and Methodical Conference Modern Scientific and Methodical Issues of Mathematics in Higher School. The conference covered modern methods used in mathematics and engineering challenges, as well as methodical issues of teaching mathematical disciplines in higher school. The materials elucidate the ways and methods of intensification of educational process and the influence of recent scientific developments on the formation of future specialists.
Keywords: інженерні задачі; математичні методи; математична освіта; mathematical methods; engineering tasks; mathematical education